REGIONAL ECONOMIC DISPARITIES IN SERBIA AND THE DEVASTATION OF RURAL AREAS IN TRANSITION - Петровић, Перо Б.; Весић, Добрица Д.; Мирковић, Адријана (Economics of Agriculture, 2011)
The differences in the development of regions, districts and municipalities in Serbia are among the highest in Europe, and the disparities between the developed North and the traditionally undeveloped south of the country is continuously deepening. Wars and tedious process of transition nineties only worsened an already diffcult situation in some areas and led to more signifcant regional disparities. The work, in accordance with the above, presents the growing regional disparities in the country, with a tendency to stress the importance of regional development management in modern conditions. Also, the report highlighted in particular the position of a group of municipalities with development issues in Serbia, the so-called. Municipalities "transitional poverty and their impact on the overall regional economic development of this country. Rural areas, as the poorest parts of the Republic, now a classic example of depopulated areas with distinct trends. Typical rural-urban migration left these areas without the presence of the active working population, rural devastated areas and thus losing any possibility of improving the existing situation.